Komunikasi Pembangunan Yang Dilakukan Taman Buaya Asam Kumbang Medan Dalam Menarik Minat Pengunjung - Frisca Nabila; Irma Yusriani Siamora; Arif Syafi’i; Fatih Ichtisam; Sabila Husna; Ummil Khoiriyah (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Development communication is a scientific discipline and communication practice in the context of developing countries, especially communication activities for planned social change. The priority of developments is activities to educate and motivate the community. In a board sense, development communication includes the role and function of communication between all parties involved in development efforts. In this case, researchers got results from The Asam Beetle Crocodile Park in Medan. Not only that, the park has received official permission from the tourism office and currently its existence is very well known to the wider community, even to people outside Sumatera.